The Role of 3D Printing in Colorectal Surgery: Current Evidence and Future Perspectives - PAPAZARKADAS, XENOFON (In Vivo, 2019)
Background: Three-dimensional (3D) printing is an emerging and evolving technology with a variety of possible applications in surgery. The purpose of this study was to examine its potential applications in the field of colorectal surgery, as a tool in pre-operative planning and peri-operative navigation, as well as in training. Its cost-efficiency was also examined. Materials and Methods: A literature review was conducted on articles specifically presenting various applications of 3D printing in the field of colorectal surgery. PubMed was the primary database researched. Results: A total of seven studies were found to meet the inclusion criteria. The majority of the articles employed 3D printing technology to produce patient-specific anatomic replicas to enhance pre-operative planning, providing satisfactory results. One study used 3D printing technology as a therapy tool, stating superior results over traditional methods. Conclusion: 3D printing is a novel technology with a broad spectrum of possible applications in colorectal surgery. Anatomic replicas specific to the anatomy of a patient with acceptable dimensional correlations can be produced using the currently available technology. Surgical and patient training can also be enhanced. Depending on the technology used, costs greatly vary and can thus hinder popularization of this technology in surgery.